Bioremediation of lead contaminated soil with Rhodobacter sphaeroides. (August 2016) - Li, Xiaomin; Peng, Weihua; Jia, Yingying; Lu, Lin; Fan, Wenhong
Abstract: Bioremediation with microorganisms is a promising technique for heavy metal contaminated soil. Rhodobacter sphaeroides was previously isolated from oil field injection water and used for bioremediation of lead (Pb) contaminated soil in the present study. Based on the investigation of the optimum culturing conditions and the tolerance to Pb, we employed the microorganism for the remediation of Pb contaminated soil simulated at different contamination levels. It was found that the optimum temperature, pH, and inoculum size for R. sphaeroides is 30–35 °C, 7, and 2 × 10 8  mL −1, respectively. Rhodobacter sphaeroides did not remove the Pb from soil but did change its speciation. During the bioremediation process, more available fractions were transformed to less accessible and inert fractions; in particular, the exchangeable phase was dramatically decreased while the residual phase was substantially increased. A wheat seedling growing experiment showed that Pb phytoavailability was reduced in amended soils. Results inferred that the main mechanism by which R. sphaeroides treats Pb contaminated soil is the precipitation formation of inert compounds, including lead sulfate and lead sulfide. Although the Pb bioremediation efficiency on wheat was not very high (14.78% root and 24.01% in leaf), R. sphaeroides remains a promising alternative for Pb remediation in contaminated soil. Highlights: Rhodobacter sphaeroides showed a certain remediation effect on Pb-contaminated soil. More available fractions were transformed to less accessible and inert fractions. Pb phytoavailability was reduced in amended soils.